DESEMPENHO DA ORGANIZAÇÃO ATRELADO AO GERENCIAMENTO DE RISCOS EM PROJETOS - Micelli, Luiz Ricardo (2009)
The vast majority of companies have now adopted the project as a manner of achieving the strategic plan set and thus achieve their goals. To drive the implementation of projects efficiently, using the area of project management as a way to plan, organize, supervise and control all aspects of the project in an ongoing process, improves performance during the performance and create the conditions for increase the chances of success. The area of project management is integrated with other management processes, including the management of risks. The risk management works in the uncertainties of projects, helping to reduce the negative effects, or threats, and enhance the positive effects, or opportunities, systematically and in the entire life cycle of the project. Despite the benefits of risk management for the project, this area is not prioritized by the companies in the planning phase. Therefore, the goal of this work is to show that this area has factors that contribute to increasing the performance of the business and competitiveness of organizations has been crucial for companies have more chances to achieve the objectives of the projects and therefore meet strategic planning, generating the results planned. As one of the ways to achieve the goal proposed a case study of risk management in a business segment oil and gas, contemplating the practical knowledge needed for this search.